Direct seeding of birch, rowan and alder can be a viable technique for the restoration of upland native woodland in the UK. (29th March 2019) - Willoughby, Ian H; Jinks, Richard L; Forster, Jack
Abstract: An experiment was established to investigate techniques for improving the reliability of direct seeding for the conversion of commercial conifer forests to native woodland. After 7 years, despite the presence of seed eating predators on site, an equivalent of between 9000 and 12 000 seedlings per hectare, depending on the initial sowing rate used, comprising a mixture of birch ( Betula pubescens Ehrh.), rowan ( Sorbus aucuparia L.) and alder ( Alnus glutinosa (L.) Gaertn.), had established in the cultivated treatments. Seed pre-treatment and sowing date had little impact on seedling numbers, but cultivation was beneficial. Very few seedlings occurred naturally in the unsown control plots. Our work suggests direct seeding may be a viable technique for converting some less fertile, freely drained, upland restock sites to a woodland consisting of birch, alder and rowan, but only if an appropriate silvicultural regime is put in place. Sowing can be combined, on the same restock site, with enrichment planting of other native species with more expensive seed such as indigenous Scots pine ( Pinus sylvestris L.), oak ( Quercus petraea Matt. (Liebl.); ( Quercus robur L.)) and juniper ( Juniper communis L.), which may also increase resilience to extreme climatic events in the first year after seeding.